MEASLES IN LARUT, MATANG AND SELAMA: ANALYSIS AND EVALUATION OF CLINICAL CASE DEFINITIONS FOR 2015-2019 - Asraf Ahmad Qamruddin; Afiq Malek; Rozali, Asnita; Norsihimah Wahid (Malaysian Journal of Public Health Medicine, 2020)
An accurate system of identifying measles cases is critical for the measles surveillance system. The objectives were: 1) To determine the incidence rate of measles in Larut, Matang and Selama district in Perak from 2015 to 2019 2) To evaluate the measles clinical case definition by comparing the performance of the measles clinical case definition in predicting laboratory-confirmed measles case. A cross-sectional analysis was carried out looking at all suspected and laboratory-confirmed measles cases in Larut, Matang and Selama District registered on the online measles surveillance reporting system between 2015 to 2019. The sensitivity, specificity, positive predictive value and negative predictive value of the clinical case definition as confirmed by the laboratory result were calculated. The incidence rate for suspected measles showed an increasing trend from 3.96 per 100,000 population in 2015 to 28.82 per 100,000 population in 2019. For laboratory-confirmed measles cases, the incidence rate showed more variation with an increase to 36.11 per million population in 2017 from 5.67 per million population in 2015. The incidence rate later decreased to 10.99 per million population in 2018 and increased again to 24.47 per million population in 2019. The sensitivity of the clinical case definition in confirming measles was 86.67% (95% CI: 69.28%, 96.24%) , specificity 47.52% (95% CI: 41.56%, 53.52%), positive predictive value 14.95% (95% CI 12.81%, 17.36%) and negative predictive value 97.10% (93.03%, 98.83%). Measles incidence is increasing in trend. The clinical case definition is an effective tool to rule out measles in cases that failed to meet the criteria due to the high negative predictive value of the definition. However, for cases that meet the clinical case definition, laboratory confirmation or epidemiological link to a confirmed case is needed.